2017
DOI: 10.1088/1361-6382/aa8be6
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics of solutions of a hyperbolic formulation of the constraint equations

Abstract: In this paper we consider the hyperbolic formulation of the constraints introduced by Rácz. Using the numerical framework recently developed by us we construct initial data sets which can be interpreted as nonlinear perturbations of Schwarzschild data in Kerr-Schild coordinates and investigate their asymptotics. Our results suggest that, unless one finds a way to exploit the freedom to pick the free part of the initial data in some suitable way, generic initial data sets obtained by this method may violate fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(59 citation statements)
references
References 38 publications
3
56
0
Order By: Relevance
“…With no control over the asymptotics it is therefore possible that the method generates initial data sets that lack a physical interpretation. Exactly this issue has been explored recently in [10,12,19]. It was confirmed that generic solutions of these equations are not asymptotically flat (this notion is defined in Section 4 below).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…With no control over the asymptotics it is therefore possible that the method generates initial data sets that lack a physical interpretation. Exactly this issue has been explored recently in [10,12,19]. It was confirmed that generic solutions of these equations are not asymptotically flat (this notion is defined in Section 4 below).…”
Section: Introductionmentioning
confidence: 90%
“…In this subsection we introduce data sets (without imposing the constraints yet) of Kerr-Schild form. Such data sets were the basis of our previous work in [10,12] and we shall continue to use them in particular in Section 6.1. In this paper now we introduce such data sets as follows.…”
Section: Kerr-schild-like Data Setsmentioning
confidence: 99%
See 3 more Smart Citations